THE ELECTORAL PERFORMANCE OF THE INDIAN NATIONAL CONGRESS PARTY IN 2004 PARLIAMENTARY ELECTION: A GEOGRAPHICAL ANALYSIS - KUMAR, DR. RAJEEV (Innovative Research Thoughts, 2018)
The purpose of the present study was analyzing the electoral performance of the Indian National Congress for India as a whole in the parliamentary election held in 2004. The analysis was carried out at the level of parliamentary constituency for all the 543 constituencies. The Congress was founded by an Englishman, A.O. Hume, on 27th December, 1885. It is the mother institution of almost all the other national parties in the country. It spearheaded the freedom struggle for full 62 years by virtue of which the country had attained independence in 1947. Secondly, the party from its very beginning has adopted the centrist path, which helped the party in drawing vote across the different socio-economic cleavages. These factors explain its dominance over the other political parties till now. The electoral performance of the Congress in terms of seats contested, percent vote polled and seats won in the above-mentioned election.